Towards automatic discontinuity trace extraction from rock mass point cloud without triangulation. (December 2018) - Guo, Jiateng; Wu, Lixin; Zhang, Minmin; Liu, Shanjun; Sun, Xiaoyu
Abstract: We propose a new automatic methodology for identifying discontinuity traces directly from 3D point clouds of natural rocky slopes. The potential feature points of the discontinuity traces were detected based on a 1D truncated Fourier series. To extract trace points from the potential feature points, a curvature-weighted Laplacian-like smoothing technique was used to thin these points. Finally, the trace lines were constructed through a feature-parameter-weighted line growing algorithm. The effectiveness of the method was tested with four data sets. Additionally, the results of two of the data sets were compared with the results of CloudCompare and an existing method. Finally, the area density was calculated based on the extracted trace lines. The results show that the proposed discontinuity trace extraction method is fast, effective and automatic and has the potential for use as a supplement to traditional direct measurements of discontinuity traces, thereby providing important supplemental data for fracture related research.